Gender Disparities in the Prevalence of Obesity and its Determinants among Younger Adults in Southern India - Mufida Begum; Keerthika M; Sowmiya M; Azhakesan P; Sugunadevi G (The Bioscan, 2025)
Background: Behavioural patterns and life style habits rapidly impacts on health of the young adults and it seems to be most severely influenced by the obesity epidemic worldwide which emphasizes the significance of resolving weight-related effects of the identified risk factors. The current study was aimed to identify the gender disparities in the frequency of obesity and overweight in young adults with its determinants. Methodology: The study was a prospective observational study and conducted from April 2023 to October 2023 among 504 undergraduate students those between the age group of 18–20 years in a private college of an urban area of south India, Tamilnadu. Information was collected using a pre-designed data entry form about the younger adults. Body mass index (BMI) was calculated based on weight and height measurements of study population. Results: A total of 504 (131 girls and 373 boys) younger adults, 91(24%) with boys and 38(29%) with girls were included in the study. The prevalence of overweight and obesity was, 68 (74.8%) for girls and 23 (25.2%) for boys, and 28 (73.7%) for girls and 10 (26.3%) for boys respectively. Lack of physical activity, sweet eating habits, take junk food regularly were showed significant difference (p<0.05) between boys and girls. There was no significant difference (p>0.05) in age, non-vegetarian diet, area of residence and duration of sleep between boys and girls. Conclusion: This study established that the determinants like lack of physical activity, junk food and sweet consumption had showed significant differences between overweight and obese boys and girls. Conversely unhealthy behaviors in early adulthood may contribute to chronic diseases and mental health disorders later in life, underscoring the need for gender specific preventive strategies.